2015
DOI: 10.1002/app.42111
|View full text |Cite
|
Sign up to set email alerts
|

Properties of poly(vinyl chloride) incorporated with a novel soybean oil based secondary plasticizer containing a flame retardant group

Abstract: A novel bio-based plasticizer containing flame retardant groups based on soybean oil (SOPE) was synthesized from epoxidized soybean oil (ESO) and diethyl phosphate through a ring-opening reaction. PVC blends plasticized with ESO and SOPE were prepared, respectively. Properties including rheological behavior, thermal stability, flame retardant performance, mechanical properties of PVC plasticized with ESO and SOPE were carefully studied. The results showed that the plasticized PVC blends indicated better compat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…These protons appeared to be stronger than that seen in THEIC-MR, and the absorption peak at 2.6 ppm corresponded to the protons of -(CH 2 ) n -in the THEIC-MR phosphate. 19,20 In addition, the absorption peak at 3.6 ppm was weaker than that of THEIC-MR, and all of the results indicated that THEIC-MR-phosphate was obtained.…”
Section: 18mentioning
confidence: 90%
See 1 more Smart Citation
“…These protons appeared to be stronger than that seen in THEIC-MR, and the absorption peak at 2.6 ppm corresponded to the protons of -(CH 2 ) n -in the THEIC-MR phosphate. 19,20 In addition, the absorption peak at 3.6 ppm was weaker than that of THEIC-MR, and all of the results indicated that THEIC-MR-phosphate was obtained.…”
Section: 18mentioning
confidence: 90%
“…18 In addition, a soybean oil based phosphate ester (SOPE) was prepared using the same ame retardant group. 19 All three kinds of vegetable oil based ame retardant plasticizers improved the thermal stability and ame retardancy of the PVC materials. However, the mechanical properties of the PVC materials gradually weakened with the addition of these plasticizers because many of the hydroxyl groups connected to the chemical structure of the plasticizers and reduced the plasticizing effect on the PVC.…”
Section: Introductionmentioning
confidence: 99%
“…They can readily be converted into their corresponding epoxidized oils by epoxidation, leading to materials with potential use as biobased plasticizers and matrices for green composites. Several epoxidized vegetable oils such as epoxidized linseed oil, epoxidized soybean oil (ESBO), epoxidized castor oil, epoxy octyl stearate and epoxidized cottonseed oil have been reported as environmentally friendly plasticizers for a wide variety of polymers . The use of monomeric and polymeric plasticizers has also been reported in the last decade.…”
Section: Introductionmentioning
confidence: 99%
“…CO 2 absorption peak hardly existed in pure TPU, while not in TPU1. The phenomenon proved that the composite material produced a large amount of CO 2 gas in the early stage of pyrolysis, which played a role in the early stage of combustion and inhibited the further development of the combustion process . H 2 O absorption range was about 360–400°C, ahead of 60°C compared with pure TPU, which was good for flame retardancy.…”
Section: Resultsmentioning
confidence: 99%
“…However, to a certain extent, its flammability, molten dripping nature and its potential to produce large amount of smoke and toxic gas during its burning have greatly increased the risk of fire hazard and limited its broad applications. This suggests that it is important to improve the smoke suppression and flame‐retardant properties of TPU . It has made great progress in the flame retardant properties of TPU at present.…”
Section: Introductionmentioning
confidence: 99%